Epigenetic regulation of CD8+ T cell exhaustion: recent advances and update - Li, Chunhong; Yuan, Yixiao; Jiang, Xiulin; Wang, Qiang (Frontiers in Immunology, 2025)
CD8+ T cells play a pivotal role in antiviral and antitumor immunity, yet under chronic antigen stimulation, they progressively enter a functionally impaired “exhausted” state, characterized by loss of effector functions, sustained high expression of inhibitory receptors, and a distinct transcriptional and epigenetic landscape. Recent studies have highlighted that epigenetic regulation is central to the initiation and maintenance of CD8+ T cell exhaustion. Exhausted T cells exhibit chromatin landscapes markedly different from those of effector and memory T cells, displaying an “epigenetic locking” that renders their phenotype largely irreversible. Emerging evidence highlights the central role of epigenetic and transcriptional regulation in driving and maintaining CD8+ T cell exhaustion. DNA methylation and histone modifications establish stable repressive chromatin landscapes that suppress effector gene programs. Non-coding RNAs, including microRNAs and long non-coding RNAs, fine-tune exhaustion-associated pathways post-transcriptionally, while RNA epigenetic modifications, such as m6A methylation, regulate transcript stability and translation in exhausted T cells. Transcription factors orchestrate these epigenetic and post-transcriptional networks, reinforcing exhaustion-specific gene expression profiles. Together, these interconnected mechanisms not only define the exhausted phenotype but also contribute to tumor immune evasion and therapeutic resistance. Understanding these processes provides a framework for novel strategies aimed at reversing CD8+ T cell exhaustion and improving the efficacy of cancer immunotherapy. Collectively, elucidating the epigenetic mechanisms underlying CD8+ T cell exhaustion not only deepens our understanding of its molecular basis but also provides new avenues for precision immunotherapy and individualized interventions.